2016
DOI: 10.7717/peerj.2596
|View full text |Cite
|
Sign up to set email alerts
|

Spotted hyaena space use in relation to human infrastructure inside a protected area

Abstract: Increasing human population growth has led to elevated levels of human-carnivore conflict. However, some carnivore populations have adapted to urban environments and the resources they supply. Such associations may influence carnivore ecology, behaviour and life-history. Pockets of urbanisation sometimes occur within protected areas, so that anthropogenic influences on carnivore biology are not necessarily confined to unprotected areas. In this study we evaluated associations between human infrastructure and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 47 publications
1
27
1
Order By: Relevance
“…and have previously been observed both in spotted hyaenas (Benson-Amram and Holekamp 2012) and in other carnivores (Bekoff 1989). Such an interpretation supports parallel studies in the KNP which have pointed to limited direct benefits from anthropogenic food (Belton et al 2016;Belton et al 2018a). We found no effect of social rank on visitation probabilities at the two anthropogenic sites, and our observations suggested that juveniles and to some extent subadults had the highest probabilities of visiting the anthropogenic sites, but primarily during one season.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…and have previously been observed both in spotted hyaenas (Benson-Amram and Holekamp 2012) and in other carnivores (Bekoff 1989). Such an interpretation supports parallel studies in the KNP which have pointed to limited direct benefits from anthropogenic food (Belton et al 2016;Belton et al 2018a). We found no effect of social rank on visitation probabilities at the two anthropogenic sites, and our observations suggested that juveniles and to some extent subadults had the highest probabilities of visiting the anthropogenic sites, but primarily during one season.…”
Section: Discussionsupporting
confidence: 91%
“…. The SK clan had free access to the unfenced staff village consisting of 250 houses, an enclosed staff compound, a golf course, a shop, communal areas, as well as administrative buildings beside an enclosed area with tourist accommodation (Belton et al 2016). The staff area combined with the rest camp covers 4.3 km 2 and houses approximately 2300 staff (Foxcroft et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, this difference between small animals and hyenas might be because most small mammals and birds are released from predation pressures in urban environments and other habitats heavily disturbed by humans, whereas predators become more exposed to threats from humans in such environments due to conflicts over resources desired by both parties (Bell, Rader, Peck, & Sih, ; Ripple et al, ). For instance, urbanized coyotes ( Canis latrans ), bobcats ( Lynx rufus ), and hyenas explicitly try to avoid these conflicts by primarily entering urban areas during the night and spending daylight hours in more natural settings (Belton, Cameron, & Dalerum, ; Lowry, Lill, & Wong, ).…”
Section: Discussionmentioning
confidence: 99%
“…The species’ range covers most of sub‐Saharan Africa, and they are top predators, along with lions, in most African ecosystems (Mills & Hofer, ). Human disturbance is known to increase their stress hormone concentrations and to affect several aspects of their behavior, including daily activity rhythms, den use, social interactions, vigilance, feeding habits, and habitat preferences (Belton, Cameron, & Dalerum, , , , ; Boydston, Kapheim, Watts, Szykman, & Holekamp, ; Kolowski & Holekamp, ; Pangle & Holekamp, ; Van Meter et al, ; Yirga et al, , ). Furthermore, earlier research suggests a high degree of variation in boldness and exploration traits in this species, both within and between populations; this variation is apparent even among very young individuals and occurs both when hyenas encounter lions and when they interact with novel stimuli at dens (Greenberg & Holekamp, ; Yoshida, Van Meter, & Holekamp, ).…”
Section: Introductionmentioning
confidence: 99%